CORE INSTITUTION OF VEGETABLE GROWING INDUSTRY SECTOR - V. F. Pivovarov; O. N. Pyshnaya; L. K. Gurkina; T. S. Naumenko; A. P. Lebedev (Овощи России, 2015)
All-Russian Scientific Research Institute of vegetable breeding and seed production is the biggest scientific and methodological center in field of breeding and seed production of vegetable crops. In this article, the main stages of establishment and development of the institute, the biographies of leaders of the institute who made an invaluable contribution to development of breeding of vegetable crops are presented. Highly skilled scientific team of VNIISSOK and material and technical resources and facilities allow keeping the leadership in many areas of science and breeding of vegetable crop and seed production.